THE EFFECT OF PERCEIVED EASE, TRUST, KNOWLEDGE AND PERCEIVED USEFULNESS ON THE INTENTION TO USE A TRADING APPLICATION - Merry Tenia; Lasma Ria Tampubolon; Nindya Putri; Mohd. Idris Dalimunthe (Jurnal Ekonomi, 2023)
The results show that the adjusted R Square value is 0.292 which means that 29.2% of intention to use a trading application, while the rest is influenced by other factors. Partially, the perception of convenience variable has a positive and significant effect, trust variable has a positive and significant effect, knowledge variable has a positive and significant effect, perception usefulness variable has a positive and significant effect. Simultaneous, the perception of ease, confidence, knowledge and perception usefulness have a positive and significant effect.